The Role of the Republic of Indonesia National Police in the Implementation of Restorative Justice in Handling Traffic Accidents (Case Study at Tanjung Pinang Police) - Revi, Rendi Ariza; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This research discusses the role of the Indonesian National Police in implementing restorative justice in handling traffic accident cases, focusing on the Tanjungpinang City Police as a case study. Data collection combines library research and field research, focusing on secondary legal materials and primary data from practitioners. The study regularly examines the legal framework, the role of the police as facilitators in mediation, and the practical challenges encountered in the field. The findings reveal that the police play a central role as facilitators in the mediation process between offenders, victims, and their families to achieve amicable settlements outside the formal criminal justice process. The implementation of restorative justice at the Tanjungpinang City Police is guided by Indonesian National Police Regulation Number 8 of 2021 and is primarily applied to cases involving minor injuries or material losses. However, in cases resulting in fatalities, settlements are rare as families tend to demand formal legal proceedings. The main obstacles include the limited economic capacity of offenders to fulfill compensation demands, protracted negotiations, and a lack of public understanding of restorative justice. Proposed solutions involve developing more comprehensive regulations, public education, specialized training for investigators, and facilitating compensation through social institutions or third parties. The study recommends enhanced collaboration among the police, government, and society to achieve balanced justice and restore social relations in traffic accident cases.